2020
DOI: 10.18176/jiaci.0568
|View full text |Cite
|
Sign up to set email alerts
|

Allergen Immunotherapy in the Era of SARS-CoV-2

Abstract: Despite the challenges of the SARS-CoV-2 pandemic, seasonal allergies and asthma require

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…9 For AIT initiation, 27% of SCIT prescribers used SLIT more frequently, a trend that remained stable during the post peak phase. Several authors 10,11 suggested that SLIT might be more appropriate during the pandemic because of the possibility of home-based administration and of a better safety profile, thus minimizing visits to healthcare facilities.…”
Section: Descriptive Information Was Analysed and Compared Withmentioning
confidence: 99%
“…9 For AIT initiation, 27% of SCIT prescribers used SLIT more frequently, a trend that remained stable during the post peak phase. Several authors 10,11 suggested that SLIT might be more appropriate during the pandemic because of the possibility of home-based administration and of a better safety profile, thus minimizing visits to healthcare facilities.…”
Section: Descriptive Information Was Analysed and Compared Withmentioning
confidence: 99%
“…Increasingly used over the last two decades as an alternative to subcutaneous immunotherapy, SLIT has been demonstrated to be efficacious in the treatment of the allergic patient [14]. Since SLIT enjoys an improved safety profile compared to SCIT, with the risk of severe systemic reaction quite low, it may be reasonable to convert SCIT patients to SLIT on a permanent basis so as to avoid disruption to immunotherapy [15]. At minimum, SLIT is a safe and reasonable tool in the allergist's armamentarium, particularly in the face of a pandemic with perhaps more limited access to hospital and clinic sites.…”
Section: Resuming Allergy Immunotherapymentioning
confidence: 99%
“…AIT can be continued in SARS-CoV-2 negative confirmed patients but with a prolonged injection interval 160 . Switching from subcutaneous to sublingual immunotherapy may be considered for AIT during COVID-19 161 . Skin manifestations of COVID-19 may be similar to other viral infections and drug hypersensitivity reactions (DHRs) 162,163 .…”
Section: Management Of Allergic Diseases During the Covid-19 Pandemicmentioning
confidence: 99%